Reduced Health Related Quality of Life, Increased Fatigue, and Daytime Sleepiness in Women with Hyperprolactinemia - Ernersson, Åsa; Bachrack-Lindström, Margareta; Landberg, Eva; Ekman, Bertil; Wahlberg, Jeanette (Hormone and Metabolic Research, 2023)
Prolactin has many physiological effects and seems to be involved in the human quality of life and well-being. The aim of this study was to describe health related quality of life, fatigue and daytime sleepiness in women with untreated hyperprolactinemia. In total 32 women (mean age 37.0±10.9 years) with verified hyperprolactinemia completed a questionnaire including questions on fatigue, measured with the Swedish version of the Fatigue Impact Scale (FIS), propensity to fall in sleep, measured with the Swedish version of the Epworth Sleepiness Scale (ESS), and Health related quality of life (HRQoL), measured by the Short-Form-36 scale (SF-36). For comparison Swedish normative data were used. The women were also interviewed regarding different symptoms related to hyperprolactinemia and the answers were analyzed using qualitative content analysis. HRQoL, as measured with SF-36, was significantly lower in all dimensions, except in physical function, compared to the Swedish reference population. Total FIS was 54.3 (41.1) and mean score on the ESS was 8.7 (4.2) indicating increased fatigue and deterioration in night sleep. The women felt very tired, and several of them rarely felt rested in the morning. The restless night sleep and the fatigue during the daytime got them to feel feeble and sometimes to find it difficult to concentrate, which affected both their mood and life in general. Women diagnosed with hyperprolactinemia reported deterioration in night sleep, increased rate of fatigue, and a reduced health related quality of life in comparison with the reference population.
Keywords: prolactin; hyperprolactinemia; HRQoL; SF-36